Study of the Effect of Photonic Crystals on Absorptance and Efficiency of Absorption of Two Organic Photovoltaic Cells by the Finite Element Method - Azocar-Guzman, M; Azocar-Guzman, M (2012)
The present numerical work describes the simulation and analysis of the absorptance and absorption efficiency of a solar cell, where the effect of utilizing photonic crystals as an active material of the cell was studied. The study was performed by numerical simulations using a computational code based on the Finite Element Method [1]. The results were obtained for photonic crystals with periodicity in both one and two dimensions [2]. In the first one, periodicity, thickness of the active material, and distance with respect to the electrode for hole collection were varied, and two organic materials for the active zone were tested, P3HT:PCBM and TDPT:PCBM. In the case of crystals with periodicity in two dimensions, only the period in one of the two dimensions was varied, based on the cell with the highest efficiency of absorption proposed for cells with periodic photonic crystals in one dimension. All simulations were obtained for waves with TM polarization, zero angle of incidence and wavelengths between 400 and 700 nm. Copyright © 2012 by ASME.